PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN MUSI RAWAS - Yohanes Susanto; Surajiyo Surajiyo (Creative Research Management Journal, 2020)
The Regional Financial and Asset Management Agency of Musi Rawas Regency is one ofthe Regional Apparatus Organizations that is tasked with assisting the Regent in runningthe wheels of Regional Government. The main task assumed by the Regional Financialand Asset Management Agency is to manage regional finances and assets. This task is animportant task that requires both Civil Servants and non-PNS employees to produce goodperformance. Performance is the result of a process that is referenced and measured overa certain period of time based on predetermined conditions, standards or agreements. Theapproach used in this research is survey research. Survey research examines large andsmall populations by selecting and studying large and small populations by selecting andexamining the selected sample and that population to find the incidence, distribution andrelative interactions and sociological and psychological variables. The population in thisstudy were all Civil Servants (PNS) and Non PNS in the Regional Financial and AssetManagement Agency of Musi Rawas Regency. The sample in this study were all membersof the population, so the sample in this study amounted to 60 people, consisting of 39 civilservants, 21 non civil servants and 25% of the Regional Development Planning Agency ofMusi Rawas Regency. Partially motivation has a significant effect on employeeperformance in the Regional Financial and Asset Management Agency of Musi RawasRegency